Fabrication and characterisation of AlGaAs/GaAs heterojunction bipolar transistors (HBTs) - Wang, Hong (2009)
The main objective of this work is to develop a baseline fabrication technology for GaAs-based Heterojunction Bipolar Transistor (HBTs) based on our existing clean room facilities. The developed HBT technology will be used for high frequency applications specifically for Monolithic Microwave Integrated Circuit (MMIC) applications.